Industrial Concentration and Regional Growth: Evidence from the Prefectures - Dekle, Robert (The Review of Economics and Statistics, 2002)
In this paper, we estimate the impact of dynamic externalities, using direct measures of total factor productivity (TFP) growth at the regional level. We find that, at the one-digit level, significant dynamic externalities exist for the finance, services, and wholesale and retail trade industries, but-contrary to the findings of most previous research-these externalities do not exist for the manufacturing industry.